Measurement of soluble C-type lectin-like receptor 2 in human plasma. (17th November 2015) - Kazama, Fuminori; Nakamura, Junya; Osada, Makoto; Inoue, Osamu; Oosawa, Mitsuru; Tamura, Shogo; Tsukiji, Nagaharu; Aida, Kaoru; Kawaguchi, Akio; Takizawa, Soichi; Kaneshige, Masahiro; Tanaka, Shoichiro; et al.
Abstract: Detection of platelet activation in vivo is useful to identify patients at risk of thrombotic diseases. Platelet factor 4 (PF4) and β-thromboglobulin (β-TG) are used for this purpose; however, they are easily released upon the minimal platelet activation that occurs during sampling. Soluble forms of several platelet membrane proteins are released upon platelet activation; however, the soluble form of C-type lectin-like receptor 2 (sCLEC-2) has not yet been fully investigated. Western blotting with an anti-CLEC-2 antibody showed that sCLEC-2 was released from washed human platelets stimulated with collagen mimetics. To detect sCLEC-2 in plasma, we established a sandwich enzyme-linked immunosorbent assay (ELISA) using F(ab′)2 anti-CLEC-2 monoclonal antibodies. Although plasma mixed with citrate, adenosine, theophylline and adenosine (CTAD) is needed for the PF4 and β-TG assays, effects of anti-coagulants (EDTA, citrate and CTAD) on the sCLEC-2 ELISA were negligible. Moreover, while special techniques are required for blood sampling and sample preparation for PF4 and β-TG assay, the standard blood collections procedures used in daily clinical laboratory tests have shown to suffice for sCLEC-2 analysis. In this study, we found that two forms of sCLEC-2 are released after platelet activation: a shed fragment and a microparticle-bound full-length protein, both of which are detected by the sCLEC-2 ELISA. The average concentration of sCLEC-2 in the plasma of 10 healthy individuals was 97 ± 55 pg/ml, whereas that in the plasma of 25 patients with diabetes mellitus (DM) was 149 ± 260 pg/ml. A trend towards an increase in sCLEC-2 concentration in the DM patients may reflect in vivo platelet activation in the patients, suggesting that sCLEC-2 may have clinical significance as a biomarker of in vivo platelet activation.